Effect of a Fiber D-Limonene-Enriched Food Supplement on Intestinal Microbiota and Metabolic Parameters of Mice on a High-Fat Diet - Maria Chiara Valerii; Silvia Turroni; Carla Ferreri; Michela Zaro; Anna Sansone; Alessandro Dalpiaz; Giada Botti; Luca Ferraro; Renato Spigarelli; Irene Bellocchio; Federica D'Amico; Enzo Spisni (MDPI AG, 2021)
Several studies showed that D-Limonene can improve metabolic parameters of obese mice via various mechanisms, including intestinal microbiota modulation. Nevertheless, its effective doses often overcome the acceptable daily intake, rising concerns about toxicity. In this study we administered to C57BL/6 mice for 84 days a food supplement based on D-Limonene, adsorbed on dietary fibers (FLS), not able to reach the bloodstream, to counteract the metabolic effects of a high-fat diet (HFD). Results showed that daily administration of D-Limonene (30 and 60 mg/kg body weight) for 84 days decreased the weight gain of HFD mice. After 84 days we observed a statistically significant difference in weight gain in the group of mice receiving the higher dose of FLS compared to HFD mice (35.24 ± 4.56 g vs. 40.79 ± 3.28 g, p < 0.05). Moreover, FLS at both doses tested was capable of lowering triglyceridemia and also fasting glycemia at the higher dose. Some insights on the relevant fatty acid changes in hepatic tissues were obtained, highlighting the increased polyunsaturated fatty acid (PUFA) levels even at the lowest dose. FLS was also able to positively modulate the gut microbiota and prevent HFD-associated liver steatosis in a dose-dependent manner. These results demonstrate that FLS at these doses can be considered non-toxic and could be an effective tool to counteract diet-induced obesity and ameliorate metabolic profile in mice.